Genome-wide characterization and identification of candidate CsRAV genes involved in JA pathway responses to cold stress in tea plant (Camellia sinensis) - Zhaolan Han; Huan Zhang; Pingping Li; Yu Duan; Jie Jiang; Xujun Zhu; Wanping Fang; Yuanchun Ma (Beverage Plant Research)
The APETALA2/ethylene response factor (AP2/ERF) transcription factor (TF) superfamily plays an important regulatory role in the signal transduction of plant responses to various biotic and abiotic stresses, including low temperature. RAV is a subfamily of the AP2/ERF TF family, and its members contain B3 DNA binding and AP2 DNA binding domains. RAV gene family members have been studied in many species, but little is known about their function in tea plants (Camellia sinensis). In this study, seven RAV genes were identified from the tea plant genome database and named CsRAV1-7. Based on phylogenetic analysis, the CsRAV genes were classified into three groups, with genes in the same subgroup exhibiting similar structures and conserved motifs. Out of the seven genes, CsRAV7 was the most distinct and contained a large number of motifs and the longest coding region. Moreover, analysis of cis-acting elements indicated that CsRAVs are likely responsive to both abiotic stress and phytohormones. In addition, quantitative RT-PCR analysis revealed that most CsRAV genes were differentially expressed under cold stress and exogenous MeJA application as both individual and combined treatments. Only CsRAV7 was induced in all six different treatments, suggesting that it may play a key role in JA-mediated cold stress responses in tea plants.